Vaginal microbiome and serum metabolite differences in late gestation commercial sows at risk for pelvic organ prolapse - Zoë E. Kiefer (Nature Portfolio, 2021)
Abstract Sow mortality attributable to pelvic organ prolapse (POP) has increased in the U.S. swine industry and continues to worsen. Two main objectives of this study were, (1) to develop a perineal scoring system that can be correlated with POP risk, and (2) identify POP risk-associated biological factors. To assess POP risk during late gestation, sows (n = 213) were scored using a newly developed perineal scoring (PS) system. Sows scored as PS1 (low), PS2 (moderate), or PS3 (high) based on POP risk. Subsequently, 1.5, 0.8, and 23.1% of sows scored PS1, PS2, or PS3, respectively, experienced POP. To identify biomarkers, serum and vaginal swabs were collected from late gestation sows differing in PS. Using GC–MS, 82 serum metabolite differences between PS1 and PS3 animals (P < 0.05) were identified. Vaginal swabs were utilized for 16S rRNA gene sequencing and differences in vaginal microbiomes between PS1 and PS3 animals were detected on a community level (P < 0.01) along with differences in abundances of 89 operational taxonomic units (P < 0.05). Collectively, these data demonstrate that sows with greater POP risk have differential serum metabolites and vaginal microflora. Additionally, an initial and novel characterization of the sow vaginal microbiome was determined.